The therapeutic alliance in internet interventions: A narrative review and suggestions for future research - Berger, Thomas (Psychotherapy research, 2017)
Objectives: Research on Internet interventions has grown rapidly over the recent years and evidence is growing that Internet-based treatments often result in similar outcomes as conventional face-to-face psychotherapy. Yet there are still unanswered concerns such as whether a therapeutic alliance can be established over the Internet and whether the alliance is important in this new treatment format. Methods: A narrative review of studies formally assessing the therapeutic alliance in Internet interventions was conducted. It is the first review summarizing findings on the therapeutic alliance that (i) distinguishes between different forms of Internet interventions and (ii) does not restrict itself to specific Internet-based treatment formats such as guided self-help treatments, e-mail or videoconferencing therapies. Results: Independent of communication modalities, diagnostic groups and amount of contact between clients and therapists, client-rated alliance scores were high, roughly equivalent to alliance ratings found in studies on face-to-face therapy. Mixed results were found regarding the therapist-rated alliance and alliance-outcome associations. Conclusions: The review points to the limitations of the available evidence and identifies unanswered questions. It is concluded that one of the major tasks for future research is to identify unique characteristics of the therapeutic alliance in the different treatment formats.